2012
DOI: 10.1590/s0103-507x2012000100016
|View full text |Cite
|
Sign up to set email alerts
|

Assistência multiprofissional em unidade de terapia intensiva ao paciente portador de síndrome de Prader-Willi: um enfoque odontológico

Abstract: Assistência multiprofissional em unidade de terapia intensiva ao paciente portador de síndrome de Prader-Willi: um enfoque odontológico INTRODUCTIONPrader-Labhart-Willi or Prader-Willi syndrome (PWS) was first reported in 1956, and additional syndrome details have been elucidated since then. This syndrome is primarily characterized by severe neonatal hypotonia, dysmorphic changes, retarded physical and cognitive development, early hyperphagia, obesity, sleep disorders, psychiatric and behavioral disorders, gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The oral changes observed are compatible with those present in the scientific literature with multiple dental caries [ 3 , 10 , 11 ], tooth 74 with pulp necrosis and dentoalveolar abscess, generalized enamel demineralization [ 10 ], reasonable oral hygiene [ 9 , 10 , 14 ], presence of biofilm [ 12 ], atypical unobtrusive swallowing, hypotonic tongue, and predominantly oral breathing.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The oral changes observed are compatible with those present in the scientific literature with multiple dental caries [ 3 , 10 , 11 ], tooth 74 with pulp necrosis and dentoalveolar abscess, generalized enamel demineralization [ 10 ], reasonable oral hygiene [ 9 , 10 , 14 ], presence of biofilm [ 12 ], atypical unobtrusive swallowing, hypotonic tongue, and predominantly oral breathing.…”
Section: Discussionsupporting
confidence: 81%
“…The presence of a precarious oral hygiene encounters PWS patient's systemic conditions due to the cognitive and self-care deficit associated with the patient's behavioral disturbance, evinced by a prior poor oral hygiene. Besides, it is suggested that the lack of precocious multidisciplinary support may contribute to the opportunistic disease advance [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prader-Willi syndrome (PWS) presents odontological aspects of interest. Many deleterious effects on the oral cavity were associated with this behavioral and endocrine disorder that may cause surgery and/or worsening of the clinical condition 1…”
Section: Introductionmentioning
confidence: 99%
“…A variety of oral diseases are found in patients with PWS (Table 2) such as caries,1,17,21,25–31 hypoplastic enamel,1,17,25,28,31 viscous saliva,1,17,21,25,3032 periodontal disease,25–28 tooth wear,1,26,27,31,32 dental erosion,33 rampant caries,1,29,31 oral microsomia,25,31 dental malocclusion,1,17,21,2629 candidiasis,25,27 erythematous lesions of the oral mucosa,27 increased biofilm accumulation,1,21,25,31,32 gingivitis,1,25,27,31,32 angular cheilitis, dry mouth,28 demineralization,21,25,31 dentoalveolar abscess,29,31 hypotonic tongue,21,31 mouth breathing,21,31,32 root stumps30 and a delay in tooth eruption 28Table 2Oral manifestation, referenceOral manifestation Júnior et al, 2005Scardina; Fuca; Messina, 2007Bailleuil-Forestier et al, 2008Yanagita et al, 2011Witt et al, 2011Setti et al, 2012Gardens et al, 2014Song et al, 2015Hurren, Flack, 2016 (review)Tayal et al, 2016Roman-Torres et al, 2017Olczak-Kowalczyk et al, 2018*…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation